A comparative study on the dominant leadership type of male and female managers of selected fast food chains in Iloilo City - Bacas, Michelle; Legaspi, Michelle; maquino, Fritzie Mor.; Mercado, Anne Katharine; Ortega, Myra Mae.; Tabladillo, Ma. Rezel (2004.)
This study was made to determine the dominant leadership type among male and female managers of selected fast food chains in Iloilo City, and how they deal with their subordinates given their sex status and other factors that may affect their performance such as civil status, age, length of service and educational background. Managers from five fast food chains served as the study respondents who were selected using purposive sampling. In collecting the data the researchers used the survey approach in order to obtaain valuable and relevant information about the different management type between male and female managers namely : thinking, feeling, sensing and intuition. A thinking manager is using his/her mental capacities and deals work in reality and practicality. A feeling manager usually decides on his/her emotions; he/she is easily disturbed when things are not working the way he/she expects it to happen. A sensing manager is considered as more rationale because he/she uses both feelings and mind in perceiving situations in the working place. Intuitive managers function based on their gut feeling or instinct, that are usually dominant among women. The survey questions used were adopted from the Myers-Briggs Type Indicator (MBTI),a self-assessment questionnaire that tests the personality in correspondence to the performance or leadership and management ability of an individual. A corresponding explanation of the result of the test is indicated. The analysis of the study was also patterned after the assessment of the MBTI but with some modifications to conform to the objectives of the research. Simple statistical tools such as frequency distribution and ratio and proportion were used in data processing and analysis. Among the male respondents, 55% are inclined towards the sensing function in carrying their tasks, while 36% of the female respondents are feeling managers and another 36%, sensing managers. As to civil status, of the 14 single respondents, 57% have a dominant sensing function behavior. In relation to age, managers in all age groups were found to be dominantly sensible managers. Furthermore, the study reveals that managers are more into their sensing function regardless of their educational background. Sensing function still dominates the choice of the respondents regardless the length of managerial experience.
Research Paper ( BS Management) -- [Iloilo City] : University of the Phlippines in the Visayas-College of Management, March 2004.